Digital Preservation for the Individuals - Zervos, Spiros; Vraimaki, Eftichia (Journal of Integrated Information Management, 2019)
Purpose - This is a concept paper highlighting the most important points pertaining to the development of a web service for the preservation of the digital assets of individuals. Design/methodology/approach - A commercial web service aimed at the general public for the preservation of their digital assets is outlined. It encompasses the ability to legitimately bequeath one’s digital assets to another individual in case of death or inability, and ensures the preservation and accessibility of the digital files and their metadata for a given (long) period of time, by applying the principles of digital preservation, as described by OAIS. The development and scientific challenges of this endeavor are also briefly discussed. Originality/value - The project responds to a real contemporary public need, and proposes a service which will become highly relevant in the near future. The lacking of such a service will very soon be painfully felt by the public, with the mass loss and depreciation of their personal digital assets.